Analysis of DPT and Polio Immunization Management in Infants in the Health Center Areas of South Central Timor Regency - Junia Jessy Sarupy; Muntasir, Muntasir; Christina Rony Nayoan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The basic immunization program is a strategic effort to reduce morbidity and mortality in infants from preventable diseases. This study aimed to analyze the management of the DPT and Polio immunization program for infants in the working areas of Health Centers in South Central Timor Regency, covering aspects of planning, implementation, human resources, and digital reporting systems. The study used a qualitative approach with purposive sampling at four health centers, namely Kota, Taneotop, Lotas, and Siso. Data were collected through in-depth interviews, observation, and document review, then analyzed using the Miles and Huberman model, which includes data reduction, presentation, and conclusion drawing. The results showed that most health centers had conducted vaccine and logistics planning according to standards, but were not yet fully capable of independently managing the cold chain. Immunization was carried out routinely and through mass campaigns, although challenges remained related to electricity, vaccine distribution, and limited storage facilities. In terms of human resources, only some staff had received technical training, while others had not fully developed competencies in logistics management and digital reporting. The implementation of the ASIK and SMILE applications improved the accuracy and efficiency of reporting but was not yet uniformly applied across all areas due to infrastructure and network limitations. In conclusion, the success of the immunization program in South Central Timor Regency heavily relies on data-driven planning, capacity building for staff, and the strengthening of an integrated and sustainable digital system.